Cytotoxic and anti-methicillin resistant staphylococcus aureus activities of extracts from streptomyces spp. Isolated from mineral ores - Hurtado J. (2019)
Microorganisms living under stress conditions, such as acidophilic environments, usually respond by synthesizing compounds with important biological activities. The cytotoxic and antibacterial activities against methicillin-resistant Staphylococcus aureus (MRSA) of ten strains of Streptomyces isolated from mineral ores of Peru were evaluated. Streptomyces variabilis F and S. variabilis X were more active than vancomycin against MSRA (MIC= 0.5, 0.5 and 1.0 µg/mL, respectively). Streptomyces sp. 6c, S. albidoflavus Ya4, S. champavatii Frep13 and Streptomyces sp. F1 showed selective cytotoxic activity against human adenocarcinoma of the duodenum (HuTu80) and human lung large cell carcinoma (H460). The extracts of Streptomyces sp. F1 and S. champavatii Frep13 also showed good cytotoxic activities (IC50= 2.51 and 0.36 µg/mL, respectively) against human breast adenocarcinoma (MCF-7). Interestingly, the cytotoxic activities of some of the Streptomyces extracts were very similar to that of the positive control 5-fluorouracil. PhOL Hurtado, et al. 95 (pag 94-100)